Proceedings of the 16th International Conference on Hybrid Intelligent Systems (HIS 2016) - Abraham, Ajith, 1968-; Haqiq, Abdelkrim; Alimi, Adel M.; Mezzour, Ghita; Rokbani, Nizar; Muda, Azah Kamilah (Springer, 2017)
This book presents the latest research in hybrid intelligent systems. It includes 57 carefully selected papers from the 16th International Conference on Hybrid Intelligent Systems (HIS 2016) and the 8th World Congress on Nature and Biologically Inspired Computing (NaBIC 2016), held on November 21?23, 2016 in Marrakech, Morocco. HIS - NaBIC 2016 was jointly organized by the Machine Intelligence Research Labs (MIR Labs), USA; Hassan 1st University, Settat, Morocco and University of Sfax, Tunisia. Hybridization of intelligent systems is a promising research field in modern artificial/computational intelligence and is concerned with the development of the next generation of intelligent systems. The conference?s main aim is to inspire further exploration of the intriguing potential of hybrid intelligent systems and bio-inspired computing. As such, the book is a valuable resource for practicing engineers /scientists and researchers working in the field of computational intelligence and artificial intelligence.
International conference proceedings.
Includes author index.
Keywords: Artificial intelligence -- Congresses.; Expert systems (Computer science) -- Congresses.; Fuzzy systems -- Congresses.; Neural networks (Computer science) -- Congresses.; Hybrid computers -- Congresses.; Soft computing -- Congresses.; elektronické knihy; electronic books